Tumor-Microenvironment- Responsive Size-Shrinkable Drug-Delivery Nanosystems for Deepened Penetration Into Tumors - Cheng, Xiaoliang; Li, Houli; Ge, Xuemei; Chen, Lijuan; Liu, Yao; Mao, Wenwei; Zhao, Bo; Yuan, Wei-En (Frontiers in Molecular Biosciences, 2020)
Over the years, the manipulation and clinical application of drug delivery nanosystems for cancer diseases have attracted a rapid growth of academic research interests, and some nanodrugs have been approved for clinic application. Although encouraging achievements have been made, the potency of nanomedicines in cancer treatment is far from satisfaction, and one significant reason is the inefficient penetration of nanoparticles into solid tumors. Particle size is one of the most significant features which influence diffusion ability of drug delivery system in tumor. Size-shrinkable drug delivery nanosystems possess size switchable property that can achieve passive targeting via enhanced permeability and retention (EPR) effect and transform into ultrasmall particles in tumors for deep penetration into tumor. Tumor microenvironment is characterized by acidic pH, hypoxia, up-regulated levels of enzymes and redox environment. In this review, we summarize and analyze the current research progresses and challenges in tumor microenvironment responsive size-shrinkable drug delivery nanosystems. We further expect to present some meaningful proposals and enlightenments on promoting deep penetration into tumor of nanoparticles.